Organizational Sustainability: Bibliometric Review and Research Agenda - Novita krishna; Anita Gesti Timur Sari; M Taqi Ardabilli; Jatmiko muara; Yang Junchu (SMARTINDO, 2023)
Abstract Purpose - Organizations have an important role in human life. Some of the important roles include being a place for activities, work, increasing knowledge and abilities, and achieving the targets and/or goals of the organization itself. Further research is to review how important organizational sustainability is and to find out how far an organization is able to survive in the midst of global competition. Design/methodology/approach - This study uses the Scopus metric as an Evaluation Technique where for research on Sustainability from 2020 and 2022 the highest in this research is sustainability. The relational bibliometric network visualization technique draws a global representation of the concepts and their relationships,Bibliometric Density visualization relational techniques show little research. and Relational Bilbliometric Techniques Visualization Ovelay Visualization shows new and old research, Findings and Discussion –The results of mapping using the Scopus metric are from 2020 and 2022 where the highest in this research is sustainability. Bibliometric analysis using VOSviewer with the type of analysis